2008
DOI: 10.1016/j.jvs.2008.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Increased 18F-fluorodeoxyglucose uptake in abdominal aortic aneurysms in positron emission/computed tomography is associated with inflammation, aortic wall instability, and acute symptoms

Abstract: Maximum aortic FDG uptake correlated significantly with inflammation, followed by increased MMP expression and histopathologic characteristics of aneurysm wall instability and clinical symptoms. Therefore, FDG-PET/CT might be a new diagnostic technique to study AAA disease in vivo and may contribute to improve prediction of individual AAA rupture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
146
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(156 citation statements)
references
References 24 publications
7
146
2
1
Order By: Relevance
“…Maximum fluorodeoxyglucose ( 18 F‐FDG) uptake after positron emission tomography scanning was studied as a marker for expansion in 3 studies67, 68, 69 and in 1 study as a marker for rupture 70. All 3 studies demonstrated significant inverse correlations with aneurysm expansion ( r =−0.50 [medium bias risk], r =−0.38 [low bias risk], and r =−0.32 [medium bias risk]; total n=104).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum fluorodeoxyglucose ( 18 F‐FDG) uptake after positron emission tomography scanning was studied as a marker for expansion in 3 studies67, 68, 69 and in 1 study as a marker for rupture 70. All 3 studies demonstrated significant inverse correlations with aneurysm expansion ( r =−0.50 [medium bias risk], r =−0.38 [low bias risk], and r =−0.32 [medium bias risk]; total n=104).…”
Section: Resultsmentioning
confidence: 99%
“…It therefore seems contradictive that an inverse correlation was found between 18 F‐FDG uptake and expansion in all 3 studies. The current explanation is that an inflammatory period precedes a phase of rapid growth and is then followed by a period of stasis with low metabolic activity 67, 68, 69, 70. However, this phenomenon is clearly not fully explained yet.…”
Section: Discussionmentioning
confidence: 95%
“…Current guidelines for stable patients recommend surgical or endovascular intervention based largely on aortic dimensions [82,83], although it is well known that rupture can occur in small aneurysms as well. It has been shown that abdominal aortic FDG uptake is associated with higher wall stress [84] and correlates with instability, symptoms and with macrophage infiltration [85]. Whether FDG uptake can identify patients who will benefit from earlier intervention than that dictated by size remains the subject of several ongoing studies.…”
Section: The Potential Of Fdg-pet Imaging In Aortic Aneurysm and Aortmentioning
confidence: 99%
“…In patients with abdominal aortic aneurysm (AAA), Reeps et al found that the intensity of FDG uptake in AAA was associated with progression and correlates with the number of macrophage and T-cell, higher local MMP tissue activities, and extracellular matrix degradation. 12,13 Similarly, Kuehl et al showed, in 33 patients with AAS, that vessel wall inflammation depicted by FDG-PET was found in one third of the patients.…”
Section: What Is the Rationale For Using Fdg-pet In Aas?mentioning
confidence: 92%